Adenoviral-mediated correction of methylmalonyl-CoA mutase deficiency in murine fibroblasts and human hepatocytes - Korson Mark; Sloan Jennifer; Dorko Kenneth; Tsai Matthew S; Chandler Randy J; Freeman Richard; Strom Stephen; Venditti Charles P (BMC, 2007)
Abstract Background Methylmalonic acidemia (MMA), a common organic aciduria, is caused by deficiency of the mitochondrial localized, 5'deoxyadenosylcobalamin dependent enzyme, methylmalonyl-CoA mutase (MUT). Liver transplantation in the absence of gross hepatic dysfunction provides supportive therapy and metabolic stability in severely affected patients, which invites the concept of using cell and gene delivery as future treatments for this condition. Methods To assess the effectiveness of gene delivery to restore the defective metabolism in this disorder, adenoviral correction experiments were performed using murine Mut embryonic fibroblasts and primary human methylmalonyl-CoA mutase deficient hepatocytes derived from a patient who harbored two early truncating mutations, E224X and R228X, in the MUT gene. Enzymatic and expression studies were used to assess the extent of functional correction. Results Primary hepatocytes, isolated from the native liver after removal subsequent to a combined liver-kidney transplantation procedure, or Mut murine fibroblasts were infected with a second generation recombinant adenoviral vector that expressed the murine methylmalonyl-CoA mutase as well as eGFP from distinct promoters. After transduction, [1-14C] propionate macromolecular incorporation studies and Western analysis demonstrated complete correction of the enzymatic defect in both cell types. Viral reconstitution of enzymatic expression in the human methylmalonyl-CoA mutase deficient hepatocytes exceeded that seen in fibroblasts or control hepatocytes. Conclusion These experiments provide proof of principle for viral correction in methylmalonic acidemia and suggest that hepatocyte-directed gene delivery will be an effective therapeutic treatment strategy in both murine models and in human patients. Primary hepatocytes from a liver that was unsuitable for transplantation provided an important resource for these studies.